REFORMULASI SISTEM PERENCANAAN PEMBANGUNAN NASIONAL DENGAN MODEL GBHN SEBAGAI HALUAN NEGARA - Otto Trengginas Setiawan (PARAPOLITIKA: Journal of Politics and Democracy Studies, 2021)
The change in the status of the MPR from the highest state institution to a state institution has eliminated the role of the MPR in setting outlines for state policy. Reformation does provide a political spirit and a new perspective as reflected in the amendments to the 1945 Constitution of the Republic of Indonesia, but the resulting impact is the loss of the continuity between the government and regional governments, and at every change of President. This is reflected in the vision, mission, and work program of the elected President (which is further formulated as the National RPJM / RPJMN) which turns out that in several ways (regarding the material and direction of program achievement) it is different from the vision, mission and work program of the Regional Head (Governor, Regent and Mayor) are elected, and there is no legal consequence whatsoever, because there is no single norm that regulates it. The method used in this paper is a political research method that departs from an analysis of political ideas, political institutions, political attitudes and behavior, as well as policy decision makers and political networks. The purpose of this research is to find out what form of law is most appropriate forbringing back GBHN in the Indonesian constitutional system, which institution is most appropriate for producing the GBHN, and through what kind of mechanism is the most appropriate. Therefore, the results of the analysis in this paper are to ensure the continuity of development in Indonesia today, urging the need to re-attend the State Policy Guidelines in the form of MPR Decrees produced by the MPR through the amendment mechanism of the 1945 NRI Constitution.